The relative effect of age in international football: Europe vs South America. - José María Yagüe; José María Izquierdo; Álvaro Muñoz; Joaquín Sánchez; Juan Carlos Redondo (Asociación Española de Ciencias del Deporte, 2020)
The concept of relative age effect refers to the consequences of the physical and psychological differences that may exist between those born earlier or later within the same calendar year. The objective of the present study was to examine this phenomenon in international professional football, identifying the influences of the continent. The sample comprised 6414 subjects from 225 teams (115 UEFA and 110 CONMEBOL) from the professional football Leagues (PFL). Statistical analysis was based on the Chi-squared (X2) test followed by the odds ratios (OR) and 95% confidence intervals estimation. The main results show higher RAE in the CONMEBOL leagues (OR = 2.23) than in the UEFA leagues (OR = 1.95). In addition, in all leagues analysed, except in the Premier League of England there was an over-representation of individuals born in the first few months of the year. We can conclude that the relative age effect is consistent and exists in international football.